Simultaneous Ozone and High Light Treatments Reveal an Important Role for the Chloroplast in Co-ordination of Defense Signaling - Xu, Enjun; Tikkanen, Mikko; Seyednasrollah, Fatemeh; Kangasjärvi, Saijaliisa; Brosché, Mikael (Frontiers in Plant Science, 2022)
Plants live in a world of changing environments, where they are continuously challenged by alternating biotic and abiotic stresses. To transfer information from the environment to appropriate protective responses, plants use many different signaling molecules and pathways. Reactive oxygen species (ROS) are critical signaling molecules in the regulation of plant stress responses, both inside and between cells. In natural environments, plants can experience multiple stresses simultaneously. Laboratory studies on stress interaction and crosstalk at regulation of gene expression, imply that plant responses to multiple stresses are distinctly different from single treatments. We analyzed the expression of selected marker genes and reassessed publicly available datasets to find signaling pathways regulated by ozone, which produces apoplastic ROS, and high light treatment, which produces chloroplastic ROS. Genes related to cell death regulation were differentially regulated by ozone versus high light. In a combined ozone + high light treatment, the light treatment enhanced ozone-induced cell death in leaves. The distinct responses from ozone versus high light treatments show that plants can activate stress signaling pathways in a highly precise manner.